2022
DOI: 10.1155/2022/1492239
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Induces Liver Injury by Regulating Macrophage Recruitment and Polarization via the Nrf2 Signaling Pathway

Abstract: Triptolide (TP) has limited usage in clinical practice due to its side effects and toxicity, especially liver injury. Hepatic macrophages, key player of liver innate immunity, were found to be recruited and activated by TP in our previous study. The nuclear factor-erythroid-2-related factor 2 (Nrf2) pathway exerts a protective role in TP-induced liver damage, but its effect on the functions of hepatic macrophage has not been elucidated. Here, we determined whether TP can regulate the recruitment and polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Hepatic macrophages are the most abundant hepatic immune cells which play a vital role in maintaining hepatic homeostasis and contribute to the progression of DILI ( Tsuji et al, 2020 ). Several studies have shown that TP inhibited the phagocytosis of macrophages, increased the number of macrophages, and modulated the polarization of macrophages in mice ( Wang L. et al, 2018 ; Liu L. et al, 2022 ). what’s more, in a study of TP-induced acute hepatotoxicity, researchers found that depletion of macrophages using clodronate liposomes pretreatment could suppress the inflammatory response and alleviated TP-induced hepatotoxicity ( Zhao, 2018 ).…”
Section: The Mechanisms Of Tp-induced Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic macrophages are the most abundant hepatic immune cells which play a vital role in maintaining hepatic homeostasis and contribute to the progression of DILI ( Tsuji et al, 2020 ). Several studies have shown that TP inhibited the phagocytosis of macrophages, increased the number of macrophages, and modulated the polarization of macrophages in mice ( Wang L. et al, 2018 ; Liu L. et al, 2022 ). what’s more, in a study of TP-induced acute hepatotoxicity, researchers found that depletion of macrophages using clodronate liposomes pretreatment could suppress the inflammatory response and alleviated TP-induced hepatotoxicity ( Zhao, 2018 ).…”
Section: The Mechanisms Of Tp-induced Hepatotoxicitymentioning
confidence: 99%
“…Researchers further found that the imbalance of hepatic immune homeostasis was caused by TP-induced inhibition of NF-κB-dependent transcriptional activity and CASP8 and FADD like apoptosis regulator (CFLAR, also known as FLIP) production ( Yuan et al, 2020 ). Furthermore, TP inhibited the phagocytic function of macrophages, increased the number of macrophages, and regulated macrophages polarization in the mouse liver, resulting in an amplification of the inflammatory response to a non-hepatotoxic dose of LPS and exacerbated hepatotoxicity ( Wang L. et al, 2018 ; Liu L. et al, 2022 ). Recently, it was found that the immune disorder caused by a TP-induced Th17/Treg imbalance was also the cause of liver intolerance to a non-hepatotoxic dose of LPS in TP-induced acute hepatotoxicity ( Zhang H. et al, 2022 ).…”
Section: The Mechanisms Of Tp-induced Hepatotoxicitymentioning
confidence: 99%